Development of a recombinant VP2 vaccine for the prevention of novel variant strains of infectious bursal disease virus. Issue 6 (1st November 2020) - Li, Guopan; Kuang, Hongyan; Guo, Huaxiong; Cai, Lianshen; Chu, Dianfeng; Wang, Xi; Hu, Jixiong; Rong, Jun
ABSTRACT: Since 2017, novel variant strains of infectious bursal disease virus (nvIBDV) have been detected in China, while the current vaccines on the market against very virulent IBDV have limited protection against this subtype virus. In this context, a strain of the virus has been isolated, and sequencing alignment and bird regression experiments showed that the virus was IBDV, belonging to the nvIBDV subtype (and named IBDV FJ-1812). Furthermore, the Escherichia coli expression system was used to successfully express soluble nvIBDV rVP2, which is specifically recognized by an anti-IBDV standard serum and anti-nvIBDV positive serum, and could be assembled into 14 − 17 nm virus-like particles. Based on the purified nvIBDV rVP2, we developed an IBDV FJ-1812 VP2 VLP vaccine at a laboratory scale to evaluate protection by this vaccine; in addition, we also prepared an IBDV JZ 3/02 VP2 subunit vaccine targeting very virulent IBDV and evaluated its cross-protection against nvIBDV. Results of bird experiments showed that the nvIBDV rVP2 vaccine could induce high titres of specific antibodies, completely protect the bursa of Fabricius from viral infection, and provide 100% immune protection to SPF and Ross 308 broiler chickens. Furthermore, the IBDV JZ 3/02 VP2 subunit vaccine targeting very virulent IBDV could provide 60% protection for SPF chickens and 80% protection for Ross 308 broiler chickens. This report provides important technical supports for the prevention and control of nvIBDV in the future.